The SMAC mimetic, LCL-161, reduces survival in aggressive MYC-driven lymphoma while promoting susceptibility to endotoxic shock - West, A C (Oncogenesis, 2016)
Inhibitor of apoptosis proteins (IAPs) antagonize caspase activation and regulate death receptor signaling cascades. LCL-161 is a small molecule second mitochondrial activator of caspase (SMAC) mimetic, which both disengages IAPs from caspases and induces proteasomal degradation of cIAP-1 and -2, resulting in altered signaling through the NFκB pathway, enhanced TNF production and sensitization to apoptosis mediated by the extrinsic pathway. SMAC mimetics are undergoing clinical evaluation in a range of hematological malignancies. Burkitt-like lymphomas are hallmarked by a low apoptotic threshold, conveying sensitivity to a range of apoptosis-inducing stimuli. While evaluating LCL-161 in the Eμ-Myc model of aggressive Burkitt-like lymphoma, we noted unexpected resistance to apoptosis induction despite ‘on-target' IAP degradation and NFκB activation. Moreover, LCL-161 treatment of lymphoma-bearing mice resulted in apparent disease acceleration concurrent to augmented inflammatory cytokine-release in the same animals. Indiscriminate exposure of lymphoma patients to SMAC mimetics may therefore be detrimental due to both unanticipated prolymphoma effects and increased susceptibility to endotoxic shock.